Perhitungan Bulan Dan Tanggal Baik Dalam Menentukan Pernikahan Bagi Masyarakat Pagendingan Galis Pamekasan - Mahbub, Syukron; Munib, Abdul; Wusqo, Urwatul; Hariyadi, Didik (Prodi HKI IAI Miftahul Ulum Pamekasan, 2024)
There are two main problems in this research. First, how to determine a good month and date for marriage according to the Pagendingan people. Second, the views of the Pagendingan people in determining good months and dates for marriage. This research uses a qualitative approach. The results of this research show that according to the Pagendingan community, to determine the month and date of a good wedding, they use nafi' knowledge and are based on the values ​​of Islamic teachings. According to the views of the Pagendingan community regarding determining good months and dates in marriage, there are various views, some recommend following weton, some say, weton petangan (calculation) is not recommended, all days and dates are good, but there are certain days that are considered the best. If someone already believes in weton calculations, then they should pay close attention to it with the aim of hoping for goodness from Allah SWT for what they have done.